2021
DOI: 10.1016/j.jseint.2021.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of the external glenohumeral joint rotation is associated with subacromial impingement syndrome, especially pain

Abstract: Background Subacromial impingement syndrome is a common disorder associated with functional impairment and disability of the shoulder. Internal/external glenohumeral rotation is important for shoulder function. However, because it is difficult to measure the glenohumeral joint rotation angle physically, the relationship between this angle and the clinical symptoms of subacromial impingement syndrome is still largely unknown. Using advanced cine-magnetic resonance imaging techniques, we designed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…13,14 Some studies have also used "shoulder arthroscopy" as the "gold standard" for the diagnosis of SIS, but because of its invasive nature it is often used for surgical treatment rather than as a routine preoperative examination. [15][16][17] The treatment of SIS is aimed at reducing pain and restoring function of the shoulder joint. Conservative treatment includes functional exercises, medication, closure therapy, the use of osteobiological materials and injection therapy.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Some studies have also used "shoulder arthroscopy" as the "gold standard" for the diagnosis of SIS, but because of its invasive nature it is often used for surgical treatment rather than as a routine preoperative examination. [15][16][17] The treatment of SIS is aimed at reducing pain and restoring function of the shoulder joint. Conservative treatment includes functional exercises, medication, closure therapy, the use of osteobiological materials and injection therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Subacromial impingement syndrome (IS) consists of an irritation of the rotator cuff tendons where they pass through the coracoacromial arch during shoulder elevation. This causes a narrowing acromiohumeral distance, which is thought to be the cause of subacromial IS-related pain in the anterolateral and upper shoulder, frequently reducing its functionality, mainly with regard to abduction, rotation, and flexion of over 60° ( Ishii et al, 2021 ; Michener et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it can clearly visualize the actual glenohumeral rotation. 11 , 16 In addition, it has been reported that cine-MRI could be able to obtain movements of the capsulolabrum during rotation with vivid clarity in 10 examined shoulders. 18…”
mentioning
confidence: 99%